2002
DOI: 10.1021/la011526f
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Polymer Layers as Multifunctional Interfaces

Abstract: We suggest a simple, one-step procedure to prepare a homogeneous functional polymer layer grafted to a silicon oxide substrate. We demonstrate that robust and uniform nanoscale layers can be fabricated from the functionalized hyperbranched polymer with dual nature of terminal branches:  alkyl chains combined with epoxy-functionalized chains. A branched chemical architecture with multiple epoxy groups provides the grafting capability inducing surface functionality along with simultaneous hydrophobization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Preference was given to grafting from melt to assure relatively high grafting density. For instance, Sidorenko et al 113 have reported the melt grafting of epoxy-functionalized hyperbranched polyesters (EHBP) to a bare silicon surface by the reaction of secondary epoxy groups with the hydroxyl groups at elevated temperature (Fig. 7).…”
Section: Growth and Grafting Of Hyperbranched Polymersmentioning
confidence: 99%
“…Preference was given to grafting from melt to assure relatively high grafting density. For instance, Sidorenko et al 113 have reported the melt grafting of epoxy-functionalized hyperbranched polyesters (EHBP) to a bare silicon surface by the reaction of secondary epoxy groups with the hydroxyl groups at elevated temperature (Fig. 7).…”
Section: Growth and Grafting Of Hyperbranched Polymersmentioning
confidence: 99%
“…Herein, a strategy of hyperbranched aromatic polyamide grafted AlN nanoparticles into epoxy matrix for excellent thermal properties has been proposed. Hyperbranched polymers have attracted a great deal of attention during the past decade because of their unique properties, amenability to numerous structural modifications, and potential for applications . Many reviews and books describe the range of structures that have been reported in the literature and highlight some of their interesting applications .…”
Section: Introductionmentioning
confidence: 99%
“…Due to their specific properties, as low solution viscosity and high solubility, caused by the highly branched globular structure they are considered for various applications. This is demonstrated by a variety of publications on the use of HBPs in water treatment [8], microelectronics [9,10], medical chemistry [11,12] and in coating technology [13][14][15][16][17]. In thin film applications the large amount of functional groups in HBPs is available for the interaction with "analyte" molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%